(untitled) (Third Sector Social Economic Review, 2025)
This study aims to examine the effects of mushroom management practices on employees’ organizational citizenship behavior (OCB) and organizational crab syndrome (OCS). Mushroom management refers to a leadership approach characterized by limited information sharing, exclusion from participative decision-making, and a lack of transparency intended to maintain managerial control. Data were collected from 279 healthcare professionals employed at three hospitals in Kayseri, Türkiye. Confirmatory factor analysis, correlation analysis, and multiple regression techniques were employed to analyze the data. The findings reveal that mushroom management has a significant negative effect on OCB and a significant positive effect on OCS. In particular, insufficient information sharing and fear of losing power emerged as key factors influencing these outcomes. These results underscore the detrimental impact of non-transparent and centralized leadership practices on employees’ willingness to engage in prosocial behaviors while simultaneously fostering destructive attitudes such as envy and sabotage. This study contributes to the literature on organizational behavior by revealing the dual impact of a single management style on both constructive and counterproductive work behaviors. It also offers practical insights for managers and HR professionals by highlighting the strategic importance of transparent communication and inclusive leadership in promoting employee engagement and organizational well-being.